2003
DOI: 10.1073/pnas.1533500100
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive function of androgen receptor in bone resorption

Abstract: As locally converted estrogen from testicular testosterone contributes to apparent androgen activity, the physiological significance of androgen receptor (AR) function in the beneficial effects of androgens on skeletal tissues has remained unclear. We show here that inactivation of AR in mice using a Cre-loxP system-mediated gene-targeting technique caused bone loss in males but not in females. Histomorphometric analyses of 8-week-old male AR knockout (ARKO) mice showed high bone turnover with increased bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
210
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 291 publications
(239 citation statements)
references
References 35 publications
20
210
1
5
Order By: Relevance
“…E 2 may also have positive effects on bone, reducing the risk of osteoporosis [28] and preventing fractures [29]. However, it has been established, at least in rodents, that androgen action on bone can be directly mediated by activation of AR in the absence of ER [30,31]. In addition, findings from individuals with androgen insensitivity syndrome suggest that androgens play an important role in normal male growth and maintenance of bone density which cannot be filled by estrogens [32,33].On the other hand, a recent clinical review concerning the impact of T therapy on bone health [34] concluded that the available trials do not provide convincing evidence for the efficacy of T in preventing and treating osteoporosis, and that further data on fractures need to be accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…E 2 may also have positive effects on bone, reducing the risk of osteoporosis [28] and preventing fractures [29]. However, it has been established, at least in rodents, that androgen action on bone can be directly mediated by activation of AR in the absence of ER [30,31]. In addition, findings from individuals with androgen insensitivity syndrome suggest that androgens play an important role in normal male growth and maintenance of bone density which cannot be filled by estrogens [32,33].On the other hand, a recent clinical review concerning the impact of T therapy on bone health [34] concluded that the available trials do not provide convincing evidence for the efficacy of T in preventing and treating osteoporosis, and that further data on fractures need to be accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…However, because excessive androgen production in polycystic ovary syndrome causes infertility with abnormal menstrual cycles (4,5), it is possible that AR-mediated androgen signaling also plays an important physiological role in the female reproductive system. Recently, using Cre͞LoxP system, we generated an AR-null mutant mouse line (6) and demonstrated that inactivation of AR resulted in arrest of testicular development and spermatogenesis, impaired brain masculinization, high-turnover osteopenia, and late onset of obesity in males (7)(8)(9). At the same time, no overt physical or growth abnormalities were observed in female AR Ϫ/Ϫ mice.…”
mentioning
confidence: 99%
“…Most androgen actions are mediated through the AR, a ligand-inducible transcription factor that belongs to the nuclear hormone receptor superfamily (8). In the absence of ligand, AR is located primarily in the cytoplasm as an inactive complex with heat shock proteins.…”
Section: Spinal and Bulbar Muscular Atrophy (Sbma) Is A Neurodegeneramentioning
confidence: 99%